Palliative Care and Movement Disorders. Issue 5 (October 2022) - Katz, Maya
ABSTRACT: PURPOSE OF REVIEW: This article reviews the role of palliative care in the treatment of patients with life-limiting neurodegenerative movement disorders. RECENT FINDINGS: Growing evidence indicates that palliative care significantly improves quality of life and symptom burden for people with Parkinson disease and other serious movement disorders, while reducing caregiver burnout. An emphasis on advance care planning guides goal-directed treatment recommendations. Serious illness communication skills are evidence-based methods of relaying bad medical news to patients and mapping out values and goals in a way that provides comfort, emphasizes patient autonomy, and builds coping and resiliency strategies. SUMMARY: Palliative care, when offered alongside primary medical and neurologic teams, provides an extra layer of support for people with serious illnesses. The goal of palliative care is to intensively treat total pain, which includes all of the physical, emotional, social, and spiritual distress caused by serious illness. Serious illness communication skills are key to providing empathic and goal-concordant care.